2014
DOI: 10.1016/j.chembiol.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Defining Estrogenic Mechanisms of Bisphenol A Analogs through High Throughput Microscopy-Based Contextual Assays

Abstract: Summary Environmental exposures to chemically heterogeneous endocrine disrupting chemicals (EDCs) mimic or interfere with hormone actions, and negatively impact human health. Despite public interest and the prevalence of EDCs in the environment, methods to mechanistically classify these diverse chemicals in a high throughput (HT) manner have not been actively explored. Here, we describe the use of multi-parametric, HT microscopy-based platforms to examine how a prototypical EDC, Bisphenol A (BPA), and eighteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 38 publications
(62 reference statements)
5
73
0
Order By: Relevance
“…Similarly, use of ToxCast, as we have shown here, also has the potential to identify emerging contaminants with endocrine disrupting properties before they become pervasive. For example, the bisphenol A (BPA) analogues bisphenol AF and bisphenol B were among the more endocrine active environmental chemicals tested in Phase II of ToxCast (Figure 3), and corroborated by other recent findings [12]. Use of these analogues may increase as businesses strive to find alternatives to BPA in products.…”
Section: Updated Edc Toxpi Findingssupporting
confidence: 75%
“…Similarly, use of ToxCast, as we have shown here, also has the potential to identify emerging contaminants with endocrine disrupting properties before they become pervasive. For example, the bisphenol A (BPA) analogues bisphenol AF and bisphenol B were among the more endocrine active environmental chemicals tested in Phase II of ToxCast (Figure 3), and corroborated by other recent findings [12]. Use of these analogues may increase as businesses strive to find alternatives to BPA in products.…”
Section: Updated Edc Toxpi Findingssupporting
confidence: 75%
“…One of the most dangerous class is represented by bisphenols, synthetic compounds that are used in the production of certain plastics and resins (Delfosse et al, 2015). Several bisphenols were found to be estrogenic EDCs by binding to both receptor subtypes (Stossi et al, 2014). One of the most widely diffused and dangerous synthetic xenoestrogen is bisphenol A (BPA), which is widely produced and largely diffused in the environment and in foodstuff, such as plastic bottles and thermal paper.…”
Section: Synthetic Xenoestrogens: Endocrine Disrupting Chemicals (mentioning
confidence: 99%
“…These are the first compounds we have observed that demonstrated any ability to alter the promoter binding induced by 10 nM E2, reducing ERα recruitment to the PRL array by ~80% and ~40% and significantly reducing de novo mRNA production. This is in contrast to well-studied compounds with anti-estrogenic activity such as 4HT and BZA, which antagonize the E2 transcriptional response by the recruitment of corepressor complexes that inhibit transcription, but do not alter ERα recruitment to the PRL array [15,17]. The effect was greatest in the GFP-ERα:PRL-HeLa cell line and not observed or significantly reduced with the GFP-ERβ:PRL-HeLa and the MCF-7 cell lines.…”
Section: Discussionmentioning
confidence: 95%